Efektivitas Media Sosial sebagai Sarana Promosi Pendidikan Islam: Studi Pada Madrasah Dan Pesantren - Aminullah Aminullah; Annisa Tri Ananda Dewi; Moh. Kamil; Siti Khofsah; Rausyan Fikri; Uryatul Hikmah (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2026)
. This study aims to analyze the effectiveness of social media as a promotional tool for Islamic education in madrasahs and Islamic boarding schools at An-Nashiriyah Islamic Boarding School, Bawean Island, Gresik, and to identify the factors influencing its effectiveness. The study employed a qualitative approach using a case study design and grounded research to gain an in-depth understanding of educational promotion practices through social media. Data were collected through observation, in-depth interviews, and documentation studies of various promotional activities carried out by the institution. Data analysis was conducted through the stages of data condensation, data reduction, data display, and verification to obtain valid and comprehensive findings. The results indicate that the use of social media remains focused on information dissemination and has not yet been strategically managed as part of a planned educational marketing effort. The effectiveness of social media is influenced by limitations in human resource competencies, supporting infrastructure, and the absence of structured digital management. Nevertheless, social media has proven capable of enhancing the institution’s image and visibility within the community, although it has not yet had a significant impact on increasing public interest in choosing the institution. The findings highlight the importance of strengthening digital capacity, developing content strategies, and implementing professional social media management to optimize its function as a promotional medium for Islamic education.